2004
DOI: 10.1007/s11176-005-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Partition constants of α-aminophosphonates in two-phase aqueous-organic solvent systems

Abstract: Two-phase potentiometric titration was used to determine partition constants for a series of a-aminophosphonates (RO) 2 P(O)CH 2 NR 1 R 2 [R = Alk (C 2 3C 5 ), R 1 , R 2 = Me, Et, (CH 2 ) 5 ] between water and organic solvents, such as chloroform, carbon tetrachloride, toluene, octane, n-octanol, nitrobenzene, o-xylene, and cyclohexane. Correlations between the partition constants and the number of carbon atoms in substrate molecules were obtained. Solvent effects on partition constants were discussed, and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…We observed linear correlations between the distribution constant and number of carbon atoms in the amino phosphonate molecule, irrespective of particular organic phase. The regression equations obtained [6] show that the logarithm of the distribution constant of amino phosphonates containing more than 20 carbon atoms exceeds 6, i.e., the extractant loss due to its transfer to the aqueous phase will be negligible.When choosing the particular extractant, we also took into account its chemical stability. As shown in [7], amino phosphonates containing a primary or secondary nitrogen atom tend to disproportionate when kept for a long time in a condensed phase.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…We observed linear correlations between the distribution constant and number of carbon atoms in the amino phosphonate molecule, irrespective of particular organic phase. The regression equations obtained [6] show that the logarithm of the distribution constant of amino phosphonates containing more than 20 carbon atoms exceeds 6, i.e., the extractant loss due to its transfer to the aqueous phase will be negligible.When choosing the particular extractant, we also took into account its chemical stability. As shown in [7], amino phosphonates containing a primary or secondary nitrogen atom tend to disproportionate when kept for a long time in a condensed phase.…”
mentioning
confidence: 95%
“…We observed linear correlations between the distribution constant and number of carbon atoms in the amino phosphonate molecule, irrespective of particular organic phase. The regression equations obtained [6] show that the logarithm of the distribution constant of amino phosphonates containing more than 20 carbon atoms exceeds 6, i.e., the extractant loss due to its transfer to the aqueous phase will be negligible.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Variation of substituents at the phosphorus, -carbon, and nitrogen atoms over a wide range showed that the most selective extractants were those aminophosphoryl reagents which contained more than 20 carbon atoms; in this case, the optimal hydrophilic-lipophilic balance was achieved. It should be emphasized specially that the above information was deduced by analysis of correlations between the number of carbon atoms in the extractant molecules and their distribution constants in waterorganic solvent systems [7]. Therefore, the latter parameter is necessary to elucidate the structure-property relations with a view to effect subsequent purposeful synthesis of extractants, bioactive, and other potentially useful substances possessing an optimal combination of the desired characteristics.…”
mentioning
confidence: 99%
“…The extraction coefficients were calculated by Gran's linearization of the titration curves, as we previously described for phase distribution of a-aminophosphonates [4]. The resulting log extraction constants are listed in the table.…”
mentioning
confidence: 99%